Synthesis and applications of MOF - derived porous nanostructures - Yap, Min Hui; Fow, Kam Loon; Chen, George Zheng (Elsevier, 2017)
Metal organic frameworks (MOFs) represent a class of porous material which is formed by strong bonds between metal ions and organic linkers. By careful selection of constituents, MOFs can exhibit very high surface area, large pore volume, and excellent chemical stability. Research on synthesis, structures and properties of various MOFs has shown that they are promising materials for many applications, such as energy storage, gas storage, heterogeneous catalysis and sensing. Apart from direct use, MOFs have also been used as support substrates for nanomaterials or as sacrificial templates/precursors for preparation of various functional nanostructures. In this review, we aim to present the most recent development of MOFs as precursors for the preparation of various nanostructures and their potential applications in energy-related devices and processes. Specifically, this present survey intends to push the boundaries and covers the literatures from the year 2013 to early 2017, on supercapacitors, lithium-ion batteries, electrocatalysts, photocatalyst, gas sensing, water treatment, solar cells, and carbon dioxide capture. Finally, an outlook in terms of future challenges and potential prospects towards industrial applications are also discussed.